DD-06 SPIN (SURGICAL PRACTICES IN INCISIONAL HERNIA REPAIR). A NATIONAL TRAINEE-LED COLLABORATIVE MULTICENTRE PROSPECTIVE OBSERVATIONAL STUDY. (13th October 2022) - Kingston, J; Tarazi, M; Burns, K; Kirwan, C; Moinuddin, Z; Van Dellen, D
Abstract: Aim: There is currently no established UK database establishing reliable outcome data for surgical repair of incisional herniae (IH). Their heterogeneity (variability in size, patient comorbidity, and multiple repair techniques) has resulted in no surgical management or outcome reporting consensus. This study aims to utilise national trainee led research collaboratives to perform a multi-centre, observational, prospective study to assess variation in IH defects (by utilising pre-defined criteria from The European Hernia Society (EHS) classification for IH and a Modified Ventral Hernia Working Group) and their subsequent operative management. This study will yield valuable, standardised data on variation in practice and outcomes (complications and 3 and 12-months follow-up) to provide a platform for expanding IH research. Materials and Methods: All NHS hospitals in England undertaking elective IH repair will be eligible for inclusion. Dissemination of and recruitment to the study will be driven by regional research collaborative networks. This study will include all elective adult IH repairs with. Data will be collected and managed using REDCap electronic data capture tool. There will be three distinct phases comprising; Retrospective data collection from regional centres to validate research protocol. Surgeon questionnaire to establish trends in surgical technique and IH management. Prospective observational study investigating patient selection, pre-operative workup, techniques for IH repair (including surgical adjuncts), outcome data and quality of life questionnaires using a validated tool (HerQLes). The study is currently unfunded. Funds are sought to obtain NHS Trust sponsorship and proceed to phase 3 of the study.